Antibody (IgG, IgA, and IgM) to baker's yeast (Saccharomyces cerevisiae), yeast mannan, gliadin, ovalbumin and betalactoglobulin in monozygotic twins with inflammatory bowel disease. Issue 7 (July 1992) - Lindberg, E; Magnusson, K E; Tysk, C; Järnerot, G
Abstract : To assess whether dietary antigens play a role in inflammatory bowel disease, 26 monozygotic twin pairs with inflammatory bowel disease and 52 healthy controls were investigated for serum antibodies (IgA, IgG, IgM) against ovalbumin, betalactoglobulin, gliadin, whole yeast (Saccharomyces cerevisiae) and yeast cell wall mannan. The twins were made up of five pairs concordant and nine pairs discordant for Crohn's disease, and two pairs concordant and 10 pairs discordant for ulcerative colitis. Two patients with Crohn's disease had a slight increase in disease activity, the others were in clinical remission. Two striking observations were made: first, individuals with ulcerative colitis were indistinguishable from healthy twins, and controls except for the response to gliadin. Both healthy and diseased twins had higher IgA levels to gliadin than controls. Second, twins who had developed Crohn's disease displayed higher antibody titres towards yeast cell wall mannan in particular, but also to whole yeast (Saccharomyces cerevisiae) of all antibody types (IgA, IgG, and IgM). In contrast, the response to gliadin, ovalbumin, and betalactoglobulin did not differ from healthy twins and was even lower than in the controls. The results argue against an increased systemic antigen presentation caused by an impaired mucosal barrier in the inflammatory bowel disease. Rather, they suggest that yeast cell wall material–that is, mannan, or some antigen rich in mannose and cross reacting with mannan, may play an aetiological role in Crohn's disease, but not in ulcerative colitis. The increases in IgA and IgM, as well as IgG suggest that local and systemic immune systems are selectively activated by antigen(s) present in the cell wall of baker's yeast.